(untitled) (Bangladesh Journal of Pharmacology, 2016)
The effect of Cynomorium flavonoids on mice model of perimenopausal depression was studied. Ovariectomized female mice (n=70) were randomly divided into 7 groups evenly and treated with different concentrations (5-400 mg/mL, of cynomorium flavonoids, gengnian’an capsule and soy isoflavones soft capsule. The model related groups were applied with different stress for consecutive 18 days. Behavior tests were performed on the 27th, 28th, and 29th days of administration. The concentrations of estradiol (E2), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) in serum as well as the 5-hydroxytryptamine (5-HT) and dopamine (DA) in brain homogenates were determined after the last administration. It was found that cynomorium flavonoids have significant effects on the mice with perimenopausal depression.